PENGARUH PEMBERIAN TUNJANGAN SERTIFIKASI GURU DAN MOTIVASI KERJA TERHADAP KINERJA GURU MIPA SMA DI KABUPATEN JAYAPURA - Karo-Karo, Sinarta Daud; Walukow, Auldry F. (Magister Pendidikan IPA, UNCEN, 2013)
The research of the effect of teacher certification allowancess and work motivation on senior high school mathematic and natural science teacher performance in Jayapura regency. This research aims to know the effect of certification benefits (X1), work motivation (X2), and with the same allowances teacher certification (X1), work motivation (X2), on senior high school mathematic and natural science teachers performance in Jayapura regency (Y). Type of the research is a quantitative from of correlation. Sampling technique us saturated sample. The results showed (1) there is strong relationship between the variables of teacher certification (X1) to performance benefits of senior high school mathematic and natural science teachers in Jayapura regency (Y) at r = 0,595. While the donations of teacher certification to the performance benefit of senor high school mathematic and natural science techers in Jayapura regency at r square = 0,354 = 35,40%. (2) There is strong relationship between the variables of work motivation (X2) to the performance of senior high school mathematic and natural science teachers in Jayapura regency (Y) at r = 0,679, while the donations of work motivation to the performance benefit of senior high school mathematic and natural science teachers in Jayapura regency at r Square = 0,461 = 46,10%. (3) With the magnitude of variable allowances teacher certification (X1) and work motivation (X2) to the performance of senior high school mathematic and natural science teachers in Jayapura regency (Y) at r = 0,709, this means there is strong relationship between teacher certification allowances and work motivation jointly on the performance of teachers of senior high school mathematic and natural science teachers in Jayapura regency, The magnitude of teacher certification allowances and motivation to work together on teacher performance and motivation work collectively equal to the perormance of senior high school mathematic and natural science teacher in Jayapura regency at r square = 0,502 = 50,20%. The result of this study showed the significant effect between teacher certiication allowances, work motivation and the madnitude of teacher certification allowances and work motivation to the perormance of senior high school mathematic and natural science teachers in jayapura regency. Key words: Allowances teacher certification. Teacher work motivation, teacher perormance